Experimental study on lean-burn characteristics of an SI engine with hydrogen/gasoline combined injection and EGR. (21st May 2019) - Yu, Xiumin; Guo, Zezhou; He, Ling; Dong, Wei; Sun, Ping; Du, Yaodong; Li, Zhe; Yang, Hang; Wang, Sen; Wu, Haiming
Abstract: Hydrogen has shown potential for improving the combustion and emission characteristics of the spark ignition (SI) dual-fuel engine. To reduce the additional NOx emissions caused by hydrogen direct injection, in this research, the cooperative control of the addition of hydrogen with exhaust gas recirculation (EGR) in the hydrogen/gasoline combined injection engine was investigated. The results indicate that both the addition of hydrogen and the use of EGR can increase the brake mean effective pressure (BMEP). As the αH2 value increases from 0% to 25%, the maximum BMEP increases by 9%, 12.70%, 16.50%, 11.30%, and 8.20%, respectively, compared with the value without EGR at λ = 1.2. The CA0-10 tends to increase with increases in the EGR rate. However, the effect of EGR in increasing the CA0-10 can be offset by the addition of 15% hydrogen at λ = 1.2. Measurements of the coefficient of variation of the indicated mean effective pressure (COVIMEP ) indicate that the addition of hydrogen can effectively extend the EGR limit. Regarding gaseous emissions, NOx emissions, after the introduction of EGR and the addition of hydrogen, are lower than those of pure gasoline without EGR. An 18% EGR rate yields a significant reduction in NOx, reaching maximum decreases of about 82.7%, 77.8%, and 60% compared to values without EGR at λ = 1.0, 1.2, and 1.4, respectively. As the EGR rate increases, the hydrocarbon (HC) emissions continuously increase, whereas a blend of 5% hydrogen can significantly reduce the HC emissions at high EGR rates at λ = 1.4. Finally, according to combustion and emissions, the coupling of a 25% addition of hydrogen with 30% EGR at λ = 1.2, and the coupling of a 20% addition of hydrogen with an 18% EGR rate at λ = 1.4 yield the best results. Highlights: The addition of H2 and use of EGR can increase the brake mean effective pressure. The effect of EGR on increasing CA0-10 can be offset by 15% addition of H2 at λ = 1.2. The addition of H2 can effectively reduce the COVIMEP and extend the EGR limit. The combination of EGR and H2 addition generates lower NOx than those of gasoline. The addition of 20% H2 with 18% EGR rate provides the best condition at λ = 1.4.